PENGARUH CREATIVITY DAN PROACTIVE PERSONALITY TERHADAP ENTREPRENEURIAL INTENTION YANG DIMEDIASI OLEH ENTREPRENEURIAL SELF-EFFICACY PADA MAHSISWA PROGRAM SARJANA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Roudha tillah; Hamdi Harmen (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This research ains to measure the effect of creativity and proactive personality of entrepreneurial intention mediated by entrepreneurial self-efficacy to undergraduate students of the Faculty of Economics and Business, Syiah Kuala University. Data were collected throught a survey of 246 respondents as sample to represent the research populating technique used in this research was probability sampling by type stratified random sampling. Structural equation modeling (SEM) was used as analytical method to determine the effect between the variabels involved. The results of the study found that creativity and entrepreneurial self-efficacy significantly affect entrepreneurial intention. However, The results did find a entrepreneurial self-efficacy was able to mediate the effect of creativity and proactive personality to entrepreneurial intention. The results didn’t find a significant effect between proactive personality and entrepreneurial intention.